The Effectiveness of Training and Work Discipline on Individual Quality and Performance - Affandy Agusman Aris; Lukman. S; Moh. Akhtar Setia Ramadhan Eka Diningrat; Widyawati; Muhammad Rais Rahmat Razak (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This study has significant implications for both theoretical and practical knowledge in human resource management. Theoretical implications include the reinforcement of critical concepts in human capital and motivational theories. However, the practical consequences are particularly noteworthy. The study provides actionable insights for organizations to enhance work discipline and individual quality through targeted training and development programs, thereby improving employee performance. The originality of this study lies in its detailed analysis of the mediating role of a particular quality, a relatively unexplored area in previous research.